The impact of terrorism on tourism demand in Pakistan - Kakar, Mehmood Khan; Waliullah, Waliullah (2008)
The terrorist attacks of September 11, 2001 in the United States (US) exposed the vulnerabilities of the tourism industry to changes in perception as to travel safety and security. Terrorism and threats to national security are documented to have impacts on tourism demand. Tourism activities are multi-pronged with mostly positive impact on any economy. This study attempts to investigate impacts of terrorist incidents in Pakistan. The proposed approach is a stated OLS and Autorgrasive distributed lag Modem (ARDL) model from 1985 to 2008 taken at different points in time in relation to terrorist attacks. Results show that the attacks caused a shock to tourists’ utility, and a change in the image profile of destinations. Moreover, it was found that destination experienced a strongly negative impact on their image and attractiveness.